Intertextualidade nas atividades de leitura em livros didáticos do ensino fundamental - Morais, Adriana Negreiros de Almeida (2023)
In our communicative practices, intertextuality appears as a constitutive resource of the text, since a text is always established based on a previous one with which, in some way, it is related. Therefore, it is relevant to study the relationships established between texts in the activities present in textbooks. Therefore, this research has the general objective of analyzing the theoretical approaches, types and discursive functions of intertextuality in Portuguese Language textbooks for Elementary School Final Years, considering the form of approach that these books provide. To this end, I followed the theoretical perspective of Textual Linguistics, which discusses the assumptions of intertextuality, an important linguistic resource for enriching Portuguese language classes. In this context, my research is descriptive and qualitative and follows the inductive method, since I observed the peculiarities of the approach to theories of intertextuality present in textbooks based on particular findings about the presence of intertextuality in discursive genres and the analysis of aspects inherent to the phenomenon. The general methodological data were analyzed in light of the theoretical conceptions of Piègay-Gros (1996), Koch; Bentes and Cavalcante (2008); Koch and Elias (2014); and Cavalcante (2011) on the concept and typifications of intertextuality. I was also guided by the BNCC (2020) guidelines for analyzing the corpus, which is made up of two collections of Portuguese language textbooks. Each collection consists of four books, one for each grade that makes up Elementary School Final Years. In these books, I highlighted and analyzed 18 activities that deal with intertextuality in the reading sections. The choice of these collections is justified by the following criteria: a) to be used in the teaching of the Portuguese Language for Elementary School Final Years, in public and private schools in Fortaleza; and b) comply with the requirements of the National Common Curricular Base (BNCC) – which dialogues with curricular documents and guidelines produced in recent decades, such as the National Curricular Parameters (PCN) – and the guide of the National Textbook Program (PNLD). I found, through analysis, that some Elementary School Final Years textbooks analyzed adopt an essentially superficial treatment regarding the work with theories of intertextuality in the activities of the reading sections, and, sometimes, they deal with the phenomenon without working directly , their theories or work on them in a vague way. Thus, there are still teaching manuals that partially disregard the criteria for the formation of a proficient reader, as successful reading helps the student to understand the possibilities of constructing meaning in texts, identifying existing textual resources and intertexts. participants in the interaction activity.